Red. prof. dr. Emil Tokarz – sedemdesetletnik - Jesenšek, Marko; Będkowska-Kopczyk, Agnieszka (Slavia Centralis, 2020)
Prispevek zajema opis življenja in dela red. prof. dr. Emila Tokarza ter njegovo obsežno bibliografijo.